Mechanistic role of DANCR in the choreography of signaling pathways in different cancers: Spotlight on regulation of Wnt/β-catenin and JAK/STAT pathways by oncogenic long non-coding RNA - Farooqi, A.A.; Mukhanbetzhanovna, A. A.; Yilmaz, S.; Karasholakova, L.; Yulaevna, I.M. (Non-coding RNA Research., 2021)
Discovery of non-coding RNAs has paradigmatically shifted our understanding of the multifaceted nature of cancer. It is becoming progressively more understandable that long non-coding RNAs play fundamental role in regulation of cell signaling pathways in different cancers. DANCR has started to gain remarkable appreciation because of its central role in cancer onset and progression. In this review we have attempted to summarize emerging aspects of DANCR-mediated regulation of Wnt/beta-catenin and JAK/STAT pathways in different cancers. We have also discussed how DANCR epigenetically inactivated tumor suppressors to promote cancer. There is sufficient experimental evidence related to oncogenic role of DANCR in variety of cancers. However, there is a need to uncover how DANCR modulates various other oncogenic pathways in different cancers.
Keywords: Long non-coding RNAs; miRNA; Cancer; Apoptosis; Signaling